A experiência religiosa do batismo com o Espírito Santo: um estudo psicossocial = The religious experience of baptism with the Holy Spirit : a psychosocial study - Laurentino, Gabriel Alves (Ciencias sociales y religión, 2018)
This research objective is to comprehend the Religious Experience of Baptism with the Holy Spirit of Pentecostal Evangelic Christians from Assembleia de Deus. For such, it was used for data gathering the systematic observation and focal group technic. And for the data analysis it was used the Themed Analysis of Content. The results showed that the baptism with the Holy Spirit is characterized by a relation experience with God, has the same characteristics presented in the Altered State of Consciousness, his belief being featured as type “A” (Rokeach, 1981) and it’s truthfulness supported in Faith, fulfilling the social role of the baptized believer who is a model of server. It is concluded that the religious experience of Baptism with the Holy Spirit is experienced as ASC, conditioned and meaningful by the belief system in which is linked: Pentecostal Evangelic Christians, and that such experience has a strong repercussion in their lives.